2016
DOI: 10.3109/0886022x.2016.1157749
|View full text |Cite
|
Sign up to set email alerts
|

Septic acute kidney injury in critically ill patients – a single-center study on its incidence, clinical characteristics, and outcome predictors

Abstract: Purpose The objective of this study is to examine the incidence, clinical characteristics, and outcome (90-day mortality) of critically ill Chinese patients with septic AKI. Methods Patients admitted to the ICU of a regional hospital from 1 January 2011 to 31 December 2013 were included, excluding those on chronic renal replacement therapy. AKI was defined using KDIGO criteria. Patients were followed till 90 days from ICU admission or death, whichever occurred earlier. Demographics, diagnosis, clinical charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 37 publications
(30 reference statements)
2
38
1
2
Order By: Relevance
“…Infection sites that caused sepsis were also similar to those observed in a previous study [6], this is the only single-center study, which indicated that 23.3% of septic AKI patients required extracorporeal therapy, our survey is the first on a much larger scale to estimate this proportion at 25% in Chinese ICUs. Overall survival of septic AKI patients in ICUs was 60% in this survey, which is similar to the previous study in China reported by Wang et al [5].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Infection sites that caused sepsis were also similar to those observed in a previous study [6], this is the only single-center study, which indicated that 23.3% of septic AKI patients required extracorporeal therapy, our survey is the first on a much larger scale to estimate this proportion at 25% in Chinese ICUs. Overall survival of septic AKI patients in ICUs was 60% in this survey, which is similar to the previous study in China reported by Wang et al [5].…”
Section: Discussionsupporting
confidence: 70%
“…Sepsis is the leading cause of AKI; thus, between 45 and 70% of all AKI is considered to be associated with sepsis, with a high mortality rate of up to 70.2% among these patients [4]. Although mortality has decreased to some extent in recent years because of advances in technology, it is still high, ranging from 28 to 51.4% [5][6][7]. This indicates that our ability to prevent and treat septic AKI is restricted as a result of limited understanding of its pathophysiology [3].…”
Section: Introductionmentioning
confidence: 99%
“…Single-center studies published in the Journal have explored the impact of AKI in donors on renal graft survival subsequent to renal transplantation [5], the risk of AKI after transcatheter aortic valve placement [6] and quality of life, as well as the correlation of personality profiles and coping styles with clinical outcomes in ESRD patients on maintenance hemodialysis [7]. Additional publications in the Journal have also explored the frequency and clinical characteristics of invasive fungal infections in renal transplant recipients [8], the value of combination biomarkers in predicting renal impairment after a cardiovascular bypass procedure [9], the clinical characteristics of sepsis-induced AKI from China [10], post-partum renal injury from India [11] outcomes and characteristics of AKI in hospitalized patients from sub-Saharan Africa. Emerging technologies, such as bioimpedance spectroscopy-assisted volume status assessment also received prominent attention in the Journal over this period [2,12].…”
Section: Greetings To the Readersmentioning
confidence: 99%
“…Nephrology in the acute care setting is moving into an era of cooperation and interaction between several disciplines to address the complex needs stemming from the patients' multi-faceted problems. We should remember that in most settings, renal replacement therapy in the Intensive Care Units is still associated with at least 50% in mortality rate [10,[16][17][18] obviously, the current status quo of practice (and knowledge) is insufficient and the one thing that cannot be justified is inertia. To mention just a few examples, there is exciting literature emerging on fluid overload and volume determination in critically ill patients with acute kidney injury (AKI) [19][20][21][22], the impact of other organ failures (liver, heart) in AKI [23], on peritoneal dialysis as a viable alternative for continuous renal replacement therapy [24,25] and on the uniqueness of medication dosing in those with critical illness receiving renal replacement therapy [26,27].…”
Section: Greetings To the Readersmentioning
confidence: 99%
“…A systematic review [ 1 ] containing 154 studies showed that the pooled incidence rates of AKI were 21.6% in adults (95% CI, 19.3–24.1) and 33.7% in children (95% CI, 26.9–41.3). Nowadays, decreased renal perfusion, nephrotoxic medications [ 2 ] and sepsis [ 3 ] are considered as main causes for AKI. Among of them, contrast, which is widely used in enhanced radiation technology and interventional techniques, has attracted much attention from clinical investigators.…”
Section: Introductionmentioning
confidence: 99%